Validation of Sustainable Tourism Supply Chain Management Framework Model With SEM-AMOS Application - Hermawan, Andri; Kartini, Nuri; Muhamad, Muhamad (Jurnal Toursci, 2025)
Background. The management of the tourism supply chain that exists today, when viewed from the reality on the ground, has occurred but is done traditionally, or in other words, it is not managed correctly, so the ultimate goal of supply chain management is not achieved. Aim. The author has formulated a Sustainable Tourism Framework Model based on FGDs and surveys of tourism supply chain actors. Methods. The authors used this study's research methodology: 1. Determine the title and research objectives; 2. Create an overview of the research in an abstract narrative, 3. Conduct a Literature Review on several topics related to the keywords in the abstract; 4. Research stages should be made in which the methodology is determined in detail beforehand; 5. Conduct FGD to discover the Decision Making System Model in implementing TSCM.6. Make SEM Model Design Forms.7. Entering data into the AMOS application. 8. Re-test the results of the AMOS application to optimal results. 9. Optimal Reconstruction of the SEM Model Design. 10. Arranging questions to be carried out in Survey, 10. Collecting survey data. 11. Enter data from survey results. 12. Report on survey results based on SEM model tests through the AMOS application.Result. However, the Framework Model has not yet been accurately validated. After being validated through the SEM-AMOS application, the proposed Framework Model was changed to the Sustainable Tourism Supply Chain Management Framework Model.Conclusion. Developing the STSCM application design in Indonesia should significantly improve the tourism sector's economy. For this reason, we recommend that this be followed up on the STSCM Application Development in Indonesia.Implementation. This research will be beneficial for the Indonesian government, entrepreneurs in the tourism sector, and the tourism industry in general, especially in the tourism sector